2017
DOI: 10.5152/eej.2017.16035
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Root Canal Curvature on Wall Cleanliness in the Apical Third during Canal Preparation

Abstract: Objective: The aim of this study was to evaluate the influence of root canal curvature (curved and straight root canals), prepared using reciprocating and rotary files, on wall cleanliness during root canal treatments. Methods: Thirty curved and 30 straight human root canals were prepared using ProTaper (Dentsply), ProTaper Next (Dentsply) and Reciproc files (Dentsply) (n=20/group). The roots were split longitudinally and observed using a scanning electron microscope. Six micrographs were obtained at 1, 3 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 30 publications
2
14
0
3
Order By: Relevance
“…The results of these studies pointed to a rather equable but somewhat lower average value of the smear layer in the apical part of the canal after the application of the UNICONE file. Primarily, this could be explained by the design of the working part of the instrument and by the fact that larger spaces between the blades in the instruments with reciprocating movements allow more efficient elimination of the dentin debris [2,5,21]. These findings coincide with the results of the research where the efficiency of cleaning of two systems with a single file, one with full rotation and one with reciprocating movements, was examined [3,23].…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…The results of these studies pointed to a rather equable but somewhat lower average value of the smear layer in the apical part of the canal after the application of the UNICONE file. Primarily, this could be explained by the design of the working part of the instrument and by the fact that larger spaces between the blades in the instruments with reciprocating movements allow more efficient elimination of the dentin debris [2,5,21]. These findings coincide with the results of the research where the efficiency of cleaning of two systems with a single file, one with full rotation and one with reciprocating movements, was examined [3,23].…”
Section: Discussionsupporting
confidence: 62%
“…In the literature, there are few studies that examined the efficiency of the files with reciprocating movements in removing the smear layer [3,14,21,22,23]. The results indicate that these files have similar cleaning effects to instruments with full rotation and cannot provide complete cleaning of the canal system [2,3,21,23].…”
Section: Discussionmentioning
confidence: 99%
“…Clean root canal without smear layer is one of the basic preconditions for achieving successful endodontic treatment [12,16,17]. The fact is that effective cleaning of the canal system is hardly feasible, especially in the apical third, due to inaccessibility, small diameter of the canal where the amount, concentration and time of exposure of this part of the canal to irrigation solutions is limited [12,16,17,20,21,22].…”
Section: Discussionmentioning
confidence: 99%
“…Slightly cleaner canal and smaller amount of smear layer in the apical third using the file with reciprocating movements could be explained by design of the working part of the instrument, and its cutting efficiency with increased agitation of the irrigation solution [9,16,17]. However, the influence of the file motion dynamics in a small number of realized studies has not been confirmed [20,23,24]. There are few studies in the literature that examined the efficacy of reciprocating files regarding the removal of the smear layer from the canal walls [12,16,17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation